DAMPAK DEPRESIASI RUPIAH TERHADAP DAYA SAING DAN TINGKAT PROTEKSI KOMODITAS PADI DI KABUPATEN BADUNG - Jarek Putradi (Business Management Journal, 2016)
Fulfilling the food stock became as one of the strategic role agriculture Being the most important part as motors local economy. As illustrated the demand for rice in Badung regency which has population 602.700, and rate of rice consumption 91,88 kg percapita/year is 55.376,08 ton/year The future policy of national development in the agricultural sector is faced with a change of political order and the globalization challange. The aim of this study is to determine the competitiveness of paddy in terms of the cost of domestic resources, analyzed the government's policy regarding the protection to the producers, and other policies related to improving the competitiveness of the comodities in order to achieve food self-sufficiency in Badung regency. Data was collected by proporsional random sampling and Policy Analysis Matrix=PAM was developed for further analysis. The result showed that farmer’s activity in Badung still have competitive in financial and comparative advantage. However, the incorporation effect of policy transfer showing that both farmers and comodity system encounter 24% of declining protection. Financial and economic competitive was susceptive to exchance rate, price of output, subsidy of input and declining of prodcutivity. The output policy from anticipate depreciation of rupiah still not prosper to farmers. output subsidy that is equivalent to the it shadow price urged to do.Keywords: Depreciation, competitive, protection, paddy, Badung regency.